An Environmental-Economic Measure of Sustainable Development - Robert D. Cairns; Vincent Martinet (Center for Economic Studies and ifo Institute (CESifo), 2013)
A central issue in the study of sustainable development is the interplay of growth and sacrifice in a dynamic economy. This paper investigates the relationship among current consumption, sacrifice, and sustainability improvement in a general context and in two canonical, stylized economies. We argue that the maximin value of utility measures what is sustainable and provides the limit to growth. Maximin value is interpreted as a dynamic environmental-economic carrying capacity and current utility as an environmental-economic footprint. The time derivative of maximin value is interpreted as net investment in sustainability improvement. It is called durable savings to distinguish it from genuine savings, usually computed with discounted-utilitarian prices.
Keywords: O44; Q56; 330; sustainable development; growth; maximin; sustainability indicator